Pengaruh Pupuk Kandang Sapi dan Jarak Tanam Pada Pertumbuhan dan Produksi Jagung Manis (Zea mays saccharata Sturt.) - juna rezekinta s; ferry ezra t sitepu; ratna rosanty lahay (Jurnal Agroekoteknologi, 2018)
This study aims to know the effect of cow manure and plant spacing on the growth and yield of sweet corn (Zea mays saccharata Sturt.). This research was conducted in Desa Asam Kumbang, Medan Selayang, Medan, North Sumatra, in January - April 2016 with Split Plot Design (SPD) with the two factors, namely a spacing consists of; 70 cm x 20 cm; 70 cm x 25 cm; 70 cm x 30 cm, and treatments consisted cow manure anorganic fertilizers; 7.500 kg/ha; 15.000 kg/ha; 22.500 kg/ha. The results showed that the treatment plant spacing effect significant effect on plant height, stem diameter, number of leaves, leaf area, flowering days,  fresh weight of roots, fresh weight of shoot, fresh weight of cobs with husk sweet corn plants per plot and without husk sweet corn plants per plot. The treatment of cow manure dose significantly affected plant height, stem diameter, leaf area, leaf area index, fresh weight of roots, fresh weight of shoot, fresh weight of cobs with husks, fresh weight of cobs with husks per plot and without husks per plot. The interaction between the treatment effect is not significant for all paramameters. Hight production of fresh weight of cobs without husks per plot in anorganic fertilizers or 22.5 ton cow manure per ha and namely a plant spacing consists of 70 cm x 20 cm.Keywords: Cow Manure, Plant Spacing, Sweet Corn